ELIoT: enhancing LiFi for next-generation Internet of things - J. P. M. G. Linnartz; C. R. B. Corrêa; T. E. B. Cunha; E. Tangdiongga; T. Koonen; X. Deng; M. Wendt; A. A. Abbo; P. J. Stobbelaar; P. Polak; M. Müller; D. Behnke; et al. (EURASIP Journal on Wireless Communications and Networking, 2022)
Abstract Communication for the Internet of things (IoT) currently is predominantly narrowband and cannot always guarantee low latency and high reliability. Future IoT applications such as flexible manufacturing, augmented reality and self-driving vehicles rely on sophisticated real-time processing in the cloud to which mobile IoT devices are connected. High-capacity links that meet the requirements of the upcoming 6G systems cannot easily be provided by the current radio-based communication infrastructure. Light communication, which is also denoted as LiFi, offers huge amounts of spectrum, extra security and low-latency transmission free of interference even in dense reuse settings. We present the current state-of-the-art of LiFi systems and introduce new features needed for future IoT applications. We discuss results from a distributed multiple-input multiple-output topology with a fronthaul using plastic optical fibre. We evaluate seamless mobility between the light access points and also handovers to 5G, besides low-power transmission and integrated positioning. Future LiFi development, implementation and efforts towards standardization are addressed in the EU ELIoT project which is presented here.